EFEKTIVITAS PENERAPAN KEBIJAKAN TRADING HALT DALAM MENCEGAH PANIC SELLING AKIBAT PANDEMI COVID - 19 (STUDY PADA BURSA EFEK INDONESIA TAHUN 2020) - SANTY AJI SITOHANG; TALENTA EMMA R. MARBUN; WIE SHI WUDJUD (JURNAL ILMIAH SIMANTEK, 2021)
The purpose of this study is to: (1) find out whether the implementation of trading halt policy is effective in restraining the rateof decline of JCI on the Indonesia Stock Exchange due to the Covid-19 pandemic in 2020. (2) find out whether theimplementation of the trading halt policy is effective in preventing panic selling on the Indonesia Stock Exchange due to thecovid-19 pandemic in 2020. The method used in this research is descriptive analytical research with a qualitative approach.The results showed that: (1) The implementation of the trading halt policy was quite effective in restraining the rate of declineof the Composite Stock Price Index on the Indonesia Stock Exchange when facing the Covid-19 pandemic in 2020 so thatthe movement of the Composite Stock Price Index did not fall deeper, even a few days after the trading halt, the CompositeStock Price Index turned for the better and entered the green zone. (2) The implementation of the halt trading policy is quiteeffective in preventing panic selling on the Indonesia Stock Exchange due to the Covid-19 pandemic in 2020. When tradinghalt takes place investors have time to think rationally so as to avoid panic and emotion when making investment decisions.After trading halt finally investors returned to conduct their investment studies based on fundamental and technical analysisand proved that the movement of the Composite Stock Price Index in the IDX in 2020 did not fall deeper and even increased.